Antifungal Activity and Major Bioactive Compounds of Water Extract of Pangium edule Seed against Aspergillus flavus - Kharisma I. Listyorini; Harsi D. Kusumaningrum; Hanifah N. Lioe (International Journal of Food Science)
Pangium edule seeds are widely used as spices in Southeast Asia in a fresh and fermented form and are reported to have active compounds for food preservation. However, scientific data on the active compounds of P. edule seed that can prevent the growth of toxigenic Aspergillus flavus have not been widely reported. This research subjected to determine the antifungal activity and identify the active compounds of water extract of old and fermented seed of P. edule against A. flavus. The water extract was compared to the extracts obtained by multilevel maceration using 50% ethanol, ethyl acetate, and n-hexane as solvents. Alkaloid, saponin, phenolic compound, flavonoid, triterpenoid, and glycoside were detected qualitatively in the crude extracts. The water extract showed the best activity to suppress the growth of A. flavus, determined by the agar dilution method, with the minimum inhibitory concentration (MIC) of 12.5 and 25 mg/mL for old and fermented seed, respectively. The water extracts showed a moderate toxicity with LC50 of 100-500 μg/mL, determined by the brine-shrimp toxicity test. After fractionation using 3 kDa molecular-weight (MW) cut-off ultrafiltration membrane, two fractions, i.e., fraction with MW<3 kDa and >3 kDa, were obtained. The fraction with MW<3 kDa showed the best antifungal activity with the MIC of 6.25 and 12.5 mg/mL for old and fermented seed, respectively. LC-MS/MS profile showed that different compounds belong to fatty acid, amino acid, glycoside, and peptide were found as major active compounds in the fractionated water extract. The principal compounds and partial least-square analysis, however, suggested that fatty acid and glycoside are responsible for the antifungal activity. Hence, this study concluded that the water extract of P. edule seed had promising antifungal activity against A. flavus which was due to presence of particular compounds belong to fatty acid and glycoside.